A conceptual framework for assessing agriculture-nutrition linkages - Haddad, Lawrence J. (United Nations University, 2000)
The pathways through which agriculture affects nutrition are outlined. New evidence from the International Food Policy Research Institute (IFPRI) and the Consultative Group on International Agricultural Research (CGIAR) on specific linkages is reported. Two groupings of impacts of agriculture on nutrition are identified: specific (because food per se is being produced) and generic.Specific effects include declines in food prices (to what extent do increases in food productivity lead to declines in food prices and better diets?), own-consumption (to what extent does the production of certain foods influence their consumption within the grower households and communities?), processing and preparation (how can nutrient losses be minimized?), and plant-breeding (what can be done to make specific foods more nutritious?).Generic effects include income generation for those engaged in agriculture and those linked to it, time allocation effects (how compatible are work activities with time investments in nutrition?), impacts on household decision-making (does innovation in the sector draw influence away from nutrition decision makers?), energy and nutrient expenditures (for certain individuals, are more additional nutrients expended than generated?), and health environment effects of agricultural production.The time is right for international agricultural research to review its potential for increasing its impact on malnutrition. First, micronutrient malnutrition cannot be overcome by food fortification and supplements alone. Second, international agricultural research is being put under increased pressure to demonstrate poverty reduction; improving nutrition reduces poverty. Third, agricultural policy makers and scientists will be placed under increased pressure to be more nutrition sensitive in the context of increasing overnutrition.